2010
DOI: 10.1186/cc8943
|View full text |Cite
|
Sign up to set email alerts
|

Management of bleeding following major trauma: an updated European guideline

Abstract: IntroductionEvidence-based recommendations are needed to guide the acute management of the bleeding trauma patient, which when implemented may improve patient outcomes.MethodsThe multidisciplinary Task Force for Advanced Bleeding Care in Trauma was formed in 2005 with the aim of developing a guideline for the management of bleeding following severe injury. This document presents an updated version of the guideline published by the group in 2007. Recommendations were formulated using a nominal group process, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
490
0
51

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 736 publications
(549 citation statements)
references
References 334 publications
(365 reference statements)
8
490
0
51
Order By: Relevance
“…The JTTR does not record presence of a radial pulse as a variable, therefore for the purposes of prioritisation using START and Careflight, a surrogate systolic blood pressure of 90mmHg was taken to represent the presence of a radial pulse and absence of hypotension. 16,17 4 The primary outcome of the study was to derive the optimum ranges of each physiological parameter in isolation at predicting the need for life-saving intervention. The secondary outcome was to compare the performance of the Modified Physiological Triage Tool (MPTT), the combination of these independently derived parameters, with existing major incident triage tools.…”
Section: Methodsmentioning
confidence: 99%
“…The JTTR does not record presence of a radial pulse as a variable, therefore for the purposes of prioritisation using START and Careflight, a surrogate systolic blood pressure of 90mmHg was taken to represent the presence of a radial pulse and absence of hypotension. 16,17 4 The primary outcome of the study was to derive the optimum ranges of each physiological parameter in isolation at predicting the need for life-saving intervention. The secondary outcome was to compare the performance of the Modified Physiological Triage Tool (MPTT), the combination of these independently derived parameters, with existing major incident triage tools.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly to HTS, the evidence shows that HSD can improve haemodynamic parameters and reduce intracranial pressure [35]. Unfortunately, so far none of the studies demonstrated survival or outcome benefit associated with the use of HTS or HSD and further research is needed to clarify this issue [13,16,35,36].…”
Section: Hypertonic Saline With Dextran (Hsd)mentioning
confidence: 99%
“…The current evidence from meta-analyses showed an increased risk of death in trauma patients resuscitated with colloids [16,22]. However, a Cochrane review suggested no differences between crystalloids and colloids [27].…”
Section: Synthetic Colloidsmentioning
confidence: 99%
See 2 more Smart Citations